Front Cover. (28th December 2021) - Reisinger, Ryan R.; Corney, Stuart; Raymond, Ben; Lombard, Amanda T.; Bester, Marthán N.; Crawford, Robert J. M.; Davies, Delia; de Bruyn, P. J. Nico; Dilley, Ben J.; Kirkman, Stephen P.; Makhado, Azwianewi B.; Ryan, Peter G.; et al.
Abstract : The cover image relates to the Research Article https://doi.org/10.1111/ddi.13447 "Habitat model forecasts suggest potential redistribution of marine predators in the southern Indian Ocean" by Reisinger et al. An adult male southern elephant seal (Mirounga leonina) at Marion Island, southern Indian Ocean. Image credit: Ryan Reisinger.